DOES THE USE OF VIRTUAL PRIVATE NETWORK (VPN) AFFECT THE COLLECTION OF VALUE ADDED TAX (VAT)? - Fathir Haq Kesuma; Nurhidayati Nurhidayati (Kesatuan Press, 2022)
The increase in electronic trading transactions, both through market places and trade transactions with goods and services originating from abroad, poses its own challenges in tax collection. Trading through the Electronic System (PMSE) on intangible taxable goods and taxable services originating from outside the customs area and utilized within the customs area has been regulated by the government. However, the administration of VAT collection carried out is still conventional by providing collection obligations to overseas entrepreneurs who have exceeded significant trade limits in Indonesia. With the use of Virtual Private Network (VPN) facilities, it is as if the consumer of goods or services in Indonesia is someone who resides or consumes his goods in another country. By means of a simulation, this research shows that with this VPN the potential for digital VAT receipts from Indonesia will be lost and/or the VAT receipts will appear as if they were receipts from other countries' digital taxes.